SACRED GROVES AND BIO-DIVERSITY CONSERVATION IN A KERALA VILLAGE - Sinitha G.S
Ecological sensitivity in Hindu tradition is evident from very ancient times. The interaction of human beings with nature acquired varied forms in the Neolithic period. Even though man is eager to conquer new spaces, an ecological insight is visible and it was targeted in tune with the sayings of the Rishis, ‘Loka Samastha Sukhino Bhavanthu’. Hence they lived in harmony with nature and natural resources around. The dedication of thickly planted trees to a local deity led to a tradition of sacred groves and it became mostly the centers of Naga worship. These groves occupy a pivotal position in nourishing plants and animals, soil and water conservation. Among the hundreds of sacred groves in Kerala, Vetticode is one major sacred grove and Naga worship centre. There were more than sixty Kavus or sacred groves in the Kerala village of Vetticode, but now most of them are on the verge of destruction. A variety of factors like the encroachment of the people, increasing demographic pressure, changing belief etc were decisive in it.